Congregational Information System and Inventory of GKI Harapan Abepura, Papua - Albert T. Wairara; Remuz MB Kmurawak; Yokelin Tokoro; Samuel Mandowen (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Gereja Kristen Injili Harapan Abepura Papua processes data by conventionally collecting congregational and inventory data and recapitulating it in Microsoft Excel. This process causes the data not to be up-to-date, the process of adding inefficient data and data that is vulnerable to lose. Information systems are solutions in data management. A Data and inventory system was created to help the process of efficient data management at GKI Harapan. The waterfall is used to develop the system, consisting of requirements, design, testing, integration, and maintenance. System Modeling Methods using UML with PHP programming language using codeigniter framework and MySQL as database. The research results in system development have been carried out well and are used at GKI Harapan Abepura.